Pendidikan Berbasis Merdeka Belajar Dalam Al Quran - Shah, Akmal; Maulana, Iqbal; Kurniawan, Syukri; Marpaung, Willi Rahim; Al Farabi, Mohammad (Universitas Islam Ahmad dahlan, 2024)
The purpose of this writing is to explore the concept of independent learning (merdeka belajar) in several verses of the Quran. The method used in this research is library research, where data is collected from various sources such as books, encyclopedias, scientific journals, newspapers, magazines, and other documents. The results of this research indicate that the explanation of education based on independent learning is found in the Quran, including in Surah Al-Alaq verses 1-5, Surah Al-Mujadalah verse 11, Surah Al-Jumu'ah verse 2, and Surah Al-Kahfi verse 28. Although these verses of the Quran do not explicitly and in detail mention education based on independent learning, it can be implicitly understood from the content of the verses, which mention terms or words related to learning activities such as reading, observing, thinking, writing, having noble character, good communication skills, and others.